If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 2g + -4 = 43 Reorder the terms: -4 + 2g + 2g = 43 Combine like terms: 2g + 2g = 4g -4 + 4g = 43 Solving -4 + 4g = 43 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4g = 43 + 4 Combine like terms: -4 + 4 = 0 0 + 4g = 43 + 4 4g = 43 + 4 Combine like terms: 43 + 4 = 47 4g = 47 Divide each side by '4'. g = 11.75 Simplifying g = 11.75
| 3-3(x-4)=-3-2 | | b/9=3 | | -3(x+7)=6x-39 | | -10+9k=62 | | 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 | | 11-12x=-11s | | 4(-3x)+y=2 | | 0.166666667x=4 | | 15y+9x=30 | | 8y+7=9y-1 | | 52=4(s-67) | | 5-5cosx=0 | | 9*b+4=7 | | -26-49= | | -8(-3-2n)=104 | | -7+2(1-5s)=35 | | 9*-b+4=7 | | p/3=1/8 | | 13y-7y=18 | | 81/9*(10-1)=x | | (10i)/(6-5i) | | k^2+10k-65=-9 | | 10y+32=92 | | 8-9=39 | | 3x^2+18x-43=5 |